Effects of intralipid infusions on anti‐trophoblast antibody (ATAb)‐activities in patients with recurrent pregnancy loss: An observational report. (21st December 2021) - Rogenhofer, Nina; Mahner, Sven; von Hasselbach, Yumiko Lindgard; Thaler, Christian J.
Abstract: Problem: Some studies suggest intravenous intralipid infusions (IVIL) to be effective in the treatment of immune‐mediated pregnancy failure. To this date it remains to be established, how IVIL might protect pregnancy and therefore a specific subgroup of RPL patients that might benefit from IVIL has not been defined. Anti‐trophoblast antibodies (ATAb) have been associated with RPL and appear to mediate immune pathology. We have shown, that ATAb in vitro decrease HCG‐ and progesterone production pointing to a mechanism how ATAb interfere with normal pregnancies. We have measured ATAb‐activities in patients undergoing off label IVIL‐treatment. Method of study: Ten RPL‐patients with positive ATAb, determined by using the choriocarcinoma cellline JEG‐3 and flow cytometry as described before, and otherwise unexplained RPL, received off‐label IVIL during pregnancy. Two ATAb‐positive RPL patients preferred expectant management. In addition, ATAb‐activity was studied in pregnancies of two healthy ATAb‐negative volunteers without miscarriages. Results: In RPL patients receiving IVIL, relative ATAb‐activity decreased from an average of 56.8±17.0% to 20.8±11.0% ( P  < .001). The two RPL‐patients without IVIL, aborted at 6+3gw and 7+4gw and embryonic genetic testing revealed euploid karyotypes. During pregnancies of the two healthy ATAb‐negative individuals, ATAb‐activities remained negative (16±9.8%) without significant changes ( P  = .22). Nine of the 10 pregnancies receiving IVIL proceeded uneventful with healthy newborns ≥37gw. One patient receiving IVIL aborted at 7+6gw and embryonic genetic‐testing revealed a trisomy 16. No specific side effects concerning IVIL were noted. Conclusions: Intralipid preparations during pregnancies of ATAb‐positive RPL‐patients significantly reduce ATAb‐activities and this may indicate a therapeutic mechanism of IVIL.